Once a spy [large type] - Thomson, Keith, 1965- (Thorndike Press, 2010)
Discovering that his apartment has been blown up by would-be killers, gambler Charlie Clark figures out that his Alzheimer's patient father was once a spy for the CIA and was part of an operation that sold faulty nuclear technology to terrorists.